Respon Masyarakat Terhadap Metode Pengukuran Arah Kiblat Menggunakan Keyakinan (Studi Kasus Desa Wora Kec. Wera Kab. Bima) - Kurniawan Kurniawan (Islamic Astronomy Department, Sharia and Law Faculty, 2025)
This research is based on the community's habit of measuring the direction of the Qibla every year during Eid al-Fitr prayers in the field. Every year the village community will invite village elders to carry out measurements. With the development of the times and falak instruments, they are now easily accessible everywhere, but people still use them. the habit is the traditional method. So this research aims to determine the methods and procedures for measuring the Qibla direction carried out by Wora Village elders as well as the community's response to the method of measuring the Qibla direction being measured. This research is qualitative research with the type of field research. Meanwhile, the approach that the author uses in this research is a sociological research approach. The results of this research are first: measuring the direction of the Qibla by Wora Village elders using the belief method has a difference in Qibla direction of 13˚ 26' 32.17”. Second: The community's response to the Qibla direction measured by the village elders is. First: they tend to accept measurement methods based on long-standing habits (tradition). Second: People don't know anything about the method of measuring the Qibla direction.